Acute low back pain: Differential somatosensory function and gene expression compared to healthy no-pain controls - Starkweather, Angela R. (Clin J Pain, 2016)
OBJECTIVES: Low back pain is the second most frequently diagnosed pain condition in the United States’ and although a majority of individuals have resolution of pain during the acute period, an estimated 40% of individuals will experience persistent pain. Given the heterogenous nature of low back pain, this study sought to describe and compare somatosensory and molecular (gene expression) profiles between individuals with acute low back pain and healthy no-pain controls METHODS: Using a previously established protocol, we comprehensively assessed somatosensory parameters among 31 no-pain control participants and 31 participants with acute low back pain. Samples of whole blood were drawn to examine mRNA expression of candidate genes involved in the transduction, maintenance, and modulation of pain. RESULTS: The acute low back pain group exhibited increased pain sensitivity to cold stimuli, mechanical stimuli, including mechanical temporal summation at both the painful back area and remote location suggesting a mechanism of enhanced central nervous system excitability. In addition, deep tissue specific peripheral sensitization was suggested due to significant differences in pressure pain threshold of the painful back area, but not the remote body site. Several genes that were differentially expressed were significantly associated with somatosensory alterations identified in the acute low back pain group. DISCUSSION: Acute low back pain participants showed selective pain sensitivity enhancement and differential gene expression profiles compared to pain-free controls. Further research to characterize pain-associated somatosensory changes in the context of altered mRNA expression levels may provide insight on the molecular underpinnings of maladaptive chronic pain.